Immune Evasion of Enteroviruses Under Innate Immune Monitoring - Zhang, Ying; Li, Jingyan; Li, Qihan (Frontiers in Microbiology, 2018)
As a major component of immunological defense against a great variety of pathogens, innate immunity is capable of activating the adaptive immune system. Viruses are a type of pathogen that proliferate parasitically in cells and have multiple strategies to escape from host immune pressure. Here, we review recent studies of the strategies and mechanisms by which enteroviruses evade innate immune monitoring.